1997
DOI: 10.1136/aim.15.1.33
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiology of Acupuncture: A Viewpoint

Abstract: SummaryAcupuncture is a specialised sensory stimulation that is analysed through sensory neural pathways Therefote to understand its action we have to analyse the anatomv physiology and pharmacology of the nerious system, aided with a knowledge ot' neuroendocrinology and the chemoarchitecture of the brain. Various neural theories have been developed to explain the mechanisms of acupuncturc. lt is now evident that acupuncture reacts at local, regional (spinal cord) and Seneral (brain) levels. Thetefore, inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
12
0
4
Order By: Relevance
“…Low-frequency EA can generate long-standing analgesia. 3 An increase in the messenger RNA for pro-enkephalin in brain (pituitary) is observed for 24-48 h following acupuncture. 3 General analgesic action is seen with the use of low frequencies and local analgesic action by the use of high frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-frequency EA can generate long-standing analgesia. 3 An increase in the messenger RNA for pro-enkephalin in brain (pituitary) is observed for 24-48 h following acupuncture. 3 General analgesic action is seen with the use of low frequencies and local analgesic action by the use of high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…3 An increase in the messenger RNA for pro-enkephalin in brain (pituitary) is observed for 24-48 h following acupuncture. 3 General analgesic action is seen with the use of low frequencies and local analgesic action by the use of high frequencies. 21 Higher frequencies were not http://aim.bmj.com/ used as they release dynorphin, which has rapid starting effect but much leakage, 3 14 and may reduce mesencephalic production of encephalin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needle-induced stimulation of the Aδ nerves is both an immediate one, and one lasting several hours, perhaps due to the setting up of a tissue injury-induced galvanic current. 14 …”
Section: Modus Operandimentioning
confidence: 99%
“…Based upon the results of multiple scientific studies, various theories on the analgesic mechanism of action have been concluded. Such theories include the release of endogenous opioids such as beta-endorphins, stimulation of descending antinociceptive pathways, release of inhibitory neurotransmitters such as norepinephrine and serotonin, modulation of the hypothalamic-limbic system, activation of the pain neuromatrix, and a placebo effect [2,4,8,10,11]. However, the mechanisms of these actions are yet to be fully identified and understood.…”
Section: Introductionmentioning
confidence: 98%